Partisipasi Masyarakat Dalam Pembangunan Desa: Tantangan Undang-Undang Desa - Heru Syah Putra (Jurnal Transformasi Administrasi, 2016)
This study aims to examine the effect of individual characteristics on public participation in Indonesia. This study uses data from IFLS 5 that was conducted in 2014 and 2015 with total sample is 31.410. This study uses a linear probability model (LPM) to estimate the probability of a person participate in village's activities such as community meetings and development activities. The results shows that educated person is more likely to attend village's meetings by 8,5 percent than less-educated person. However, regarding development activities, education has a negative effect on participation. Further, gender is an crucial issue regarding participation because a woman tends to be less involved in village activities. Overall, the awareness of people on village development is relatively low because less than 50 percent respondents realize or participate in village activities. Therefore, there is a need to improve the mechanism and strategies for public participation as ordered by the Village Law.